#TITLE_ALTERNATIVE# - (NIM 10104006), NURHABIBAH
In this Final Project, we discuss a mathematical model of spatial-temporal spread of avian influenza virus among chicken population. Susceptible-Infective (SI) model known in epidemiology with diffusive terms is proposed for the transmission of the disease. In particular, we look for a necessary condition for the existence of traveling wave solutions in two cases: the absence of natural growth, and the present of natural growth of population. We also study the problem numerically, and apply the MacCormack method to solve the problem numerically. The parameters which account for the phenomenon are the average length of infective period (1/a), the contact parameter (r), the number of susceptible at initial time S0, the rate of hatch of susceptible's eggs (p), and the rate of natural death (b). The minimum speed of the traveling wave can be predicted, to give a projection as to where or when the outbreak may occur in the certain region. Discritization of model with MacCormack method can simulate the spread of Avian Influenza from the source of infective to other. The result can show there is traveling wave on spread of Avian Influenza which called epizootic wave.